Pengembangan Media Pembelajaran Pop Up Book pada Mata Pelajaran IPA Sekolah Dasar - Rizka Amelia; Ramanata Disurya; Farizal Imansyah (Journal on Education, 2024)
Pop up book learning media is a book in which there are three-dimensional images that display interesting visualizations. The use of the latest learning media such as pop up books can make it easier for students to understand the material and with this media also as a support for learning facilities. This pop up book learning media development research uses the ADDIE model which has 5 stages, namely: Analysis, Design, Development, Implementation, Evaluation. The purpose of this study was to find out how the development of pop up book learning media in elementary school science subjects. This research was conducted at SD Negeri 59 OKU in grade V which amounted to 18 students. Data collection techniques carried out are by using expert validation and questionnaires. Expert validation data and student response questionnaires are calculated using a percentage formula. The results of the three validators resulted in a score with an average value of 91.7% with very valid criteria. Then pop up book learning media is categorized as suitable for use. The results of the student response questionnaire obtained a score of 96.9% with very practical criteria. From these data, it can be concluded that the development of pop up book learning media in elementary school science subjects is valid, and learning media is very practical to use.